Overview of Post-Operative Clinical Functional Results of Patients Undergoing Total Knee Replacement Procedures at Royal Prima Hospital - Lorena Febriani Simanjuntak; Rico Alexander; Linda Chiuman (CV. Inara, 2025)
Total Knee Replacement (TKR) is a surgical procedure aimed at replacing damaged knee joints due to osteoarthritis or other conditions causing pain and dysfunction. This study aims to describe the clinical functional outcomes after TKR based on age and gender among patients at Royal Prima General Hospital, Medan. A descriptive cross-sectional design was used, involving 30 patients who underwent TKR between May and April 2025. Data were collected from medical records and assessed using the Oxford Knee Score (OKS). Statistical analysis was performed to evaluate the distribution of functional outcomes. The results showed that most patients were aged 71–82 years (53.5%) and female (76.7%). Younger patients (56–60 years) achieved better clinical function (Excellent category), while older patients (71–82 years) tended to have Moderate scores. Females demonstrated better clinical outcomes than males. The study concludes that age and gender influence post-TKR clinical function, with younger and female patients showing superior outcomes